HYDROTHERMAL PROCESSING (HTP) OF ALGAE GROWN IN HTP WASTE STREAMS - ZHANG, YUANHUI; SCHIDEMAN, LANCE (2011)
A process for the conversion of organic waste to biofuel is provided comprising cultivating organisms in the aqueous product of the HTP conversion process.